Harnessing nanoparticles for immune modulation. Issue 7 (July 2015) - Getts, Daniel R.; Shea, Lonnie D.; Miller, Stephen D.; King, Nicholas J.C.
Highlights NPs can be generated from numerous biocompatible compounds. Specific physiochemical characteristics can be manipulated to modulate the immune response. Severe inflammation can be treated using NP-based approaches. Antigen delivery via NPs can restore peripheral immune tolerance.